Tanggungjawab dan pelaksanaan zakat kalangan minoriti Muslim Thailand - Waeamrene Waepa,; Shofian Ahmad,; Mohd. Nasran Mohamad,; Muhamad Razak Idris, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
Contributing zakat or alms is one of the most important Muslim obligations. This religious duty applied to all Muslims include those who live as a minority in a non-Muslim majority state. Muslim scholars such as Mahmud Shaltut, Yusuf al-Qaradawi and Zulfikar compare the obligation of contemporary Muslim minority with those in Mecca during the early period of Islam. They were required to give zakat although the method used is different compared to the Medinah period where they are a majority. This study suggests that contemporary Muslim minority in Thailand -in term of implementation- could use the methods applied to Muslim majority country. This suggestion is due to the special rights given to the Muslim community in Thailand compared to Muslim minority in other countries. Thai Muslims have a political and administrative rights which enable them to perform religious duties such as zakat which are guaranteed by the constitution of Thailand.